2013
DOI: 10.1103/physrevb.88.155130
|View full text |Cite
|
Sign up to set email alerts
|

Crystal electric field ofP2-NaxCoO2for the intermediate spin state of Co

Abstract: The magnetic moment per Co 4+ of P2(γ)-type NaxCoO2 in Curie-Weiss metal regime is revisited and examined under a newly proposed modification of the octahedral crystal electric field (CEF). The proposed model explains the origin of the existence of the intermediate state S=1 for Co 3+ through an exciton-like elementary excitation of the narrow gap between the split eg and t2g groups. The CoO2 layer is proposed to be constructed from the tilted edge-sharing square-planar CoO2 chains with inter-chain coupling. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(32 reference statements)
1
9
0
Order By: Relevance
“…3, it is intriguing to note that an activation behavior with a gap of ∼2.6 meV is implied. It is clear that α is not only temperature-dependent, as noted previously, [17] but displays field-dependence when the same temperature range is chosen in the paramagnetic regime.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…3, it is intriguing to note that an activation behavior with a gap of ∼2.6 meV is implied. It is clear that α is not only temperature-dependent, as noted previously, [17] but displays field-dependence when the same temperature range is chosen in the paramagnetic regime.…”
supporting
confidence: 67%
“…1(c)), the temperaturedependent Curie constant (C = N µ 2 ef f /3k B ) for N a 0.82 CoO 2 has been revealed from the Curie-Weiss law (χ = χ • + C T −Θ ) analysis by using the homogeneous susceptibility χ(T)=M/T data from different temperature sections above ∼5 T N . [17] The Curie constants were found to be persistently higher than the value expected from the spin-only S=1/2 of Co 4+ . In particular, the Curie constant could be interpreted to arise from three contributions, including the localized spins of…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…X-ray diffraction studies have shown that the crystal structure of Na 2 Ni 2 TeO 6 can be indexed with a space group P 6 3 /mcm satisfactorily, and a 3D antiferromagnetic (AFM) spin ordering of T N ∼27 K has been proposed; however, the impact of Na ion diffusion on the crystal and spin structure has never been explored in detail, in contrast to its sister compound Na x CoO 2 which has been studied extensively and shown rich physical insights. [3][4][5][6][7][8][9]12,14 It is highly desirable to investigate the 2D structure of the Na-layer that reflects the potential field generated by the (Te/Ni)-O honeycomb sublattice and its relationship to the magnetic structure of Ni spins. In particular, due to the diffusive nature of intercalated Na ions, a unique dynamic magneto-phonon coupling of the system could be revealed through the detailed analysis of the Na ion distribution and crystal structure change as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%